Collective Memory, Cultural Transmission, and Investments - Dessí, Roberta (American Economic Review, 2008)
I study the transmission of collective memory as a mechanism for cultural transmission, in the presence of social externalities associated with individual cultural investment decisions. The younger generation's decisions depend on beliefs about the quality of existing institutions, norms, and values, which are influenced by collective memory. In culturally homogeneous societies it can be optimal to suppress negative memories while emphasizing positive ones. However, the ability to bias collective memory is costly: it may generate cultural overoptimism and overinvestment in some cases, the reverse in other cases. The scope for welfare-enhancing manipulation of collective memory is reduced, moreover, in culturally heterogeneous societies. (JEL D83, Z13)